Pattern of Thyroid Disorders: A Cross-sectional Study in a Tertiary Care Hospital of Coastal Odisha, India - Ikhita Misra; Lalit Mohan Sika; Itishree Prusty; Ishani Rath (JOURNAL OF CLINICAL AND DIAGNOSTIC RESEARCH, 2026)
Introduction: Thyroid disorders have been reported to be highly prevalent in India, particularly in coastal regions where iodine excess may contribute to structural and functional abnormalities. Data from Ear, Nose and Throat (ENT) outpatient settings in eastern India remain limited. Aim: To evaluate the demographic profile, clinical spectrum, and biochemical patterns of thyroid dysfunction among patients presenting to the Otorhinolaryngology outpatient department of a tertiary care hospital in coastal Odisha, India. Materials and Methods: This cross-sectional study was conducted in the Department of Otorhinolaryngology of Sri Jagannatha Medical College and Hospital (SJMCH), Puri, Odisha, India. The study enrolled 213 consecutive patients with clinical or biochemical evidence of thyroid dysfunction over one year. Detailed history, examination, serum Thyroid Stimulating Hormone (TSH), free Triiodothyronine (T3), Tetraiodothyronine (T4) {Chemiluminescence Immunoassay (CLIA)}, Ultrasonography (USG), and Fine Needle Aspiration Cytology (FNAC) (where indicated) were performed. Patients were classified as euthyroid, overt/subclinical hypo- or hyperthyroid using standard reference ranges. Statistical analysis used Python 3.12 (Python Software Foundation) with the SciPy (version 1.11). Results: The cohort was 88.7% female (mean age 35.14±13.54 years). Euthyroid status predominated (n=139, 65.3%), followed by hypothyroidism (n=50, 23.5%) and hyperthyroidism (n=24, 11.3%). Goitre was present in 158 (74.2%) patients including diffuse goitre (n=44, 20.7%), colloid cyst (n=38, 17.8%), and solitary thyroid nodule (n=30, 14.1%). Hormone levels differed significantly across groups (p-value